Comparison of Hospital Duration and Analysis of Harmonic Scalpel Surgery with Conventional Protocols in Patients Undergoing Thyroid Surgery: Comparison of Harmonic and Conventional Thyroidectomy - Arija, Dharmoon; Kiani, Muhammad Aamer; Nadeem, Muhammad; Nawaz, Allah; Khan, Ahmed Hassan; Mahmood, Khalid; Hamad Ullah, Rana (Pakistan Journal of Health Sciences, 2024)
A thyroidectomy is a common surgical procedure, and while traditional methods including electrocautery pose a danger of tissue damage, harmonic scalpels have recently seen a rise in their use for this purpose. Objective: To determine whether or not the Harmonic Scalpel is beneficial in dealing with patients who are undergoing thyroidectomy. Methods: This qusai-experimental study was performed at Department of Surgery, Ghulam Muhammad Mahar Medical College Sukkur from 1st October 2022 to 31st March 2023 and 60 patients were enrolled and divided into 2 equal groups for conventional and harmonic thyroidectomy. Patients with Basedow' illness or thyroid cancer were included regardless of lymph node dissection. For 5mm blood vessel division, 55kHz ultrasound pulses were employed for coagulation. Cutting and coagulation were done using active blade. A well-structured questionnaire recorded operation length, 24-hour drainage volume, hospital stay, post-operative hypocalcaemia, drain placement, RLN paralysis, and blood loss for each patient. Results: There were 78.3% females as compared to the males 21.6%. Less operation time was taken in surgery performed by harmonic scalpel as compared to conventional surgery. Significant difference was observed in intra-operative blood loss in study group. Harmonic scalpel lost 40ml blood whereas traditional surgery lost 124ml. Both research groups had similar post-operative problems. Conclusion: Harmonic scalpel thyroidectomy appeared to be the most reliable and feasible method as compared to conventional surgery protocol in relevance to intra-operative blood loss, surgery duration, total volume drainage.